Separating Golgi Proteins from Cis to Trans Reveals Underlying Properties of Cisternal Localization - Harriet T. Parsons; Tim J. Stevens; Heather E. McFarlane; Silvia Vidal‐Melgosa; Johannes Griss; Nicola Lawrence; Richard Butler; Mirta Mittelstedt Leal de Sousa; Michelle Salemi; William G. T. Willats; Christopher J. Petzold; Joshua L. Heazlewood; et al. (2019)
The order of enzymatic activity across Golgi cisternae is essential for complex molecule biosynthesis. However, an inability to separate Golgi cisternae has meant that the cisternal distribution of most resident proteins, and their underlying localization mechanisms, are unknown. Here, we exploit differences in surface charge of intact cisternae to perform separation of early to late Golgi subcompartments. We determine protein and glycan abundance profiles across the Golgi; over 390 resident proteins are identified, including 136 new additions, with over 180 cisternal assignments. These assignments provide a means to better understand the functional roles of Golgi proteins and how they operate sequentially. Protein and glycan distributions are validated in vivo using high-resolution microscopy. Results reveal distinct functional compartmentalization among resident Golgi proteins. Analysis of transmembrane proteins shows several sequence-based characteristics relating to pI, hydrophobicity, Ser abundance, and Phe bilayer asymmetry that change across the Golgi. Overall, our results suggest that a continuum of transmembrane features, rather than discrete rules, guide proteins to earlier or later locations within the Golgi stack.